Evidence for H-bonding interactions to the μ-η2:η2-peroxide of oxy-tyrosinase that activate its coupled binuclear copper site. Issue 24 (3rd March 2022) - Kipouros, Ioannis; Stańczak, Agnieszka; Culka, Martin; Andris, Erik; Machonkin, Timothy R.; Rulíšek, Lubomír; Solomon, Edward I.
Abstract : Spectroscopic and computational methods reveal H-bonding interactions between active-site waters and the μ-η 2 :η 2 -peroxide of oxy-tyrosinase, and define their effects on the Cu(ii )2 O2 electronic structure and O2 activation. Abstract : The factors that control the diverse reactivity of the μ-η 2 :η 2 -peroxo dicopper(ii ) oxy-intermediates in the coupled binuclear copper proteins remain elusive. Here, spectroscopic and computational methods reveal H-bonding interactions between active-site waters and the μ-η 2 :η 2 -peroxide of oxy-tyrosinase, and define their effects on the Cu(ii )2 O2 electronic structure and O2 activation.